Tribological Studies Of Bio-Lubricant Under High Loading Capacity - Al-Nasrawi, Hayder Saad Oleiwi (2016)
Increased severity in operating conditions coupled with the environmental and toxicity issues related with using conventional lubricants. In addition to, depletion of petroleum reserves and high prices of fossil fuels, have led to exploration of new kind of natural additives as a bio-lubricant. BP as an agricultural wastes are potential to be developed as bio-oils that to replace the petroleum products, due to their environmentally friendly characteristics, being biodegradable, nontoxic and renewable. The purpose of this study are to produce crude oil from BP as a bio additives in paraffin oil, as well as to determine their physical and tribological properties as bio-lubricant under severe operation conditions to identify their ability for lubrication. In this study, ultrasonic homogenizer had been used to mix the lubricants. Brookfield viscometer had been used to determine viscosity of lubricants under various temperatures, while viscosity index had been determined according to ASTM 02270. Tribological performance of BP as a bio-lubricant was tested using a four-ball test machine under extreme pressure conditions, according to ASTM 02783-03. Various lubricating oils (PO and P0+5%, 20%, 50% of banana peel) were tested. The experiments were run for 30 minutes under 500-1750N range of load. The temperatures were set at 27, 80, 100 °C and the sliding speed was set to 1000 RPM. The wear scar and surface roughness were measured using digital microscope and surface roughness tester, respectively. Statistical approach had been used in this the results analyzed was to identify the ability of BP for lubrication. The results focused on density, viscosity, VI, coefficient of friction, wear scar, wear volume losses, Extreme Pressure (EP) Anti-Wear (AW) properties, welding load and surface roughness, which are the basis of comparison between bio-lubricant and paraffin oil. Experimental results showed significant improvement in overall performance with increased BP content compared with paraffin oil through all parameters mentioned above. The results showed that at 100 °C, 50%BP had achieved a highest rate improved compared with paraffin oil in terms of dynamic and kinematic viscosity at rates 250.3% and 229.7% respectively and VI at rate 310.2%. Meanwhile, at 100 °C, lower value of COF at welding point was 0.086 for 50%BP followed by 20%BP, 5%BP and 1 OO%PO at values 0.089, 0.456 and 0.595 respectively. For A W and EP properties, where rates are increase in mean wear scar diameter and welding load at 100 °C of 50%BP compared with paraffin oil was 67.36% and 44.62% respectively. Values ofwelding loads at 100 oc were 1625 N, 1575 N, 1475 N and 900 N for 50%BP, 20%BP, 5%BP and 1 OO%PO respectively. The results showed that best performance was achieved by mix a 50% ofBP in the mineral oil, where COF and WSO could reach their lowest value in extreme operation conditions. As a results, banana peel as EP and A W adoitives has proven itself able for use in lubrication applications for gears and as engine oils.